The mediating role of academic motivation in the relationship between self-efficacy and learning strategies during the COVID-19 pandemic - Alesi, Marianna; Giordano, Giulia; Gentile, Ambra; Roccella, Michele; Costanza, Carola; Caci, Barbara (Frontiers in Education, 2024)
The COVID-19 pandemic restrictions imposed the use of Online Learning (OL) as the preferred tool for delivering school and academic lectures. Despite the flexibility of the OL tool, some features (such as the use of technology, lack of sense of belonging, and Internet connection) could have impacted the academic motivation of university students and their learning strategies. Therefore, the aim of the study is to clarify the role of academic motivation in the relationship between self-efficacy and learning strategies. A sample of 1069 university students (mean age: 21.72 years, SD: 4.05; 78.5% female, 20.9% male) completed self-report questionnaires about self-efficacy, learning strategies, and academic motivation. A mediation model with general SE directly predicting learning strategies considering the type of academic motivation (autonomous or controlling motivation) was run. The results showed that students’ level of academic motivation, as autonomous regulation, mediated the relationship between self-efficacy and learning strategies. Findings highlighted that in a stressful condition like the OL during the COVID-19 pandemic, low levels of self-efficacy could negatively impact strategic learning, especially with a controlled and low-regulated motivational style. Therefore, psychologists should cooperate with educators to implement clinical and psychoeducational programs aimed at fostering students’ self-efficacy.